Age and gender differences in the relationship between obesity and disability with self-perceived employment discrimination: Results from a retrospective study of an Australian national sample. (December 2021) - Keramat, Syed Afroz; Alam, Khorshed; Rana, Rezwanul Hasan; Shuvo, Suvasish Das; Gow, Jeff; Biddle, Stuart J.H.; Keating, Byron
Abstract: Background: Health status is a crucial determinant of an individuals' labour market outcomes. The present study investigates the association between obesity and disability with perceived employment discrimination within Australia. Methods: A total of 17, 174 person-year observations from the 11, 079 respondents were analysed using four waves of data from the Household, Income, and Labour Dynamics in Australia (HILDA) survey. The primary outcome examined was employment discrimination, using obesity and disability as the main exposure variables. The longitudinal random-effects regression technique was applied to investigate the between-person differences in employment discrimination associated with obesity and disability. Results: The findings suggest that more than one in ten (12.68 %) Australians experienced employment discrimination. The odds of being discriminated against while applying for a job were 1.56 times (aOR: 1.56, 95 % CI: 1.15–2.11) higher for obese than their healthy weight counterparts in youngest women. Adults with a disability had 1.89 times (aOR: 1.89, 95 % CI: 1.65–2.17) higher odds of being discriminated against than peers without disability. Conclusion: The results provide evidence that obesity and disability contribute to employment discrimination in Australia. The findings can assist government and related agencies to consider the adequacy of existing discrimination legislation and help organisations to develop appropriate policies to address discrimination against obese and disabled people in their workplaces. Highlights: More than one in ten (12.68 %) Australians perceive being discriminated against while applying for jobs. Obese adults had higher chances of being discriminated against than healthy weight peers in youngest women. The possibility of being discriminated against while applying for a job was higher for people with disability compared with their non-disabled counterparts.